Influence of thermal annealing treatment in oxygen atmosphere on grain boundary chemistry and non-ohmic properties of SnO2 center dot MnO polycrystalline semiconductors - Orlandi, Marcelo Ornaghi [UNESP]; Bueno, Paulo Roberto [UNESP]; Longo, Elson [UNESP] (Wiley-v C H Verlag Gmbh, 2008)
The present work studied the influence of thermal treatment in oxygen rich atmosphere on heterogenous junctions in Mn-doped SnO2 polycrystalline system presenting varistor behavior. The samples were prepared by conventional oxide mixture methodology, and were submitted to heat treatment in oxygen rich atmosphere at 900 degrees C for 2h. The samples were characterized by X-ray diffraction, scanning electron microscopy, dc and ac electrical measurements. The results showed that there is an evident relationship between the microstructure heterogeneity and non-ohmic electrical properties. It was found that for this SnO2 center dot MnO-based varistor system the heat treatment in oxygen rich atmosphere does not necessarily increase the varistors properties, which was related to the decrease in the grain boundary resistance. The results are compared with Co-doped SnO2 varistors and ZnO based varistors. (C) 2008 WILEY-VCH Verlay GmbH & Co. KGaA, Weinheim.